PENGARUH PENERAPAN PEMBELAJARAN SAINTIFIK TERHADAP HASIL BELAJAR PPKn DI KELAS XI SMA NEGERI 1 UJUNGBATU KABUPATEN ROKAN HULU - Fitri, Ade Krisyano; Gimin, Gimin; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The scientific approach is one of the approaches to scientific learning. Daryanto (2014) revealed that learning with a scientific approach is a learning process designed in such a way that students actively construct concepts, laws or principles through stages of observing, formulating problems, proposing or formulating hypotheses, collecting data and various techniques, analyzing data , draw conclusions and communicate concepts, laws or principles found. Learning outcomes are specific competencies or abilities both cognitive, affective and psychomotor achieved or mastered by students after attending the teaching and learning process (Kunandar, 2013) This study aims to determine the effect of applying the 2013 curriculum scientific approach to student learning outcomes in PPKn learning. This research was conducted at SMAN 1 Ujungbatu, Rokan Hulu Regency. The subject of this research was class XI students. The sample in this study was to use a homogeneity test taken at random two classes class XI IPS 1 as a control class and XI IPS 2 as an experimental class. Data collected through observation, tests and documentation. The design used is pre-test and post-test on the Quasi Experimental design. Based on the results of the Independent Sample T test differences it is known that the significance of p = 0,000. These results indicate that 0 <0.01. Means that there are differences in the influence of the scientific approach by using preetest and posttest between the control class and the experimental class. This shows that there is an influence of the application of the scientific approach to student learning outcomes. Coupled with the N-gain test results higher experimental class than the control class (0.57> 0.34). It shows that learning using the 2013 curriculum approach can improve student learning outcomes. Thus the use of a scientific approach has a positive and significant effect on student learning outcomes in PPKn subjects in class XI of SMA Negeri 1 Ujungbatu. From observations that researchers take a scientific approach in addition to improving learning outcomes also increases motivation, interest in learning and student activity.Key Words: Influence, Scientific Learning, Learning Outcomes.